The Self-Revelation of Taufiq al-Hakim in the Novel Himār al-Ḥakīm: A Carl Thompson Perspective: Kashf al-dhāt ‘inda Tawfīq al-Ḥakīm fī riwāyah Ḥimār al-Ḥakīm: Ru’yah Carl Thompson - Chilwina, Nadhita; Kholil, Ahmad; Hasaniyah, Nur (An-Nahdah Al-'Arabiyah is published by Department of Arabic Language and Literature in cooperation with The Center for Research and Community Service (LP2M), 2025)
Self-image in real life is often shaped through the interaction between personal identity and social pressures that influence how one should act. Self-image in a social context is not something static, but rather a result of dynamic construction. This study aims to analyze the self-revelation of Taufiq Al-Hakim as both an author and a character in the novel Himār Al-Hakīm. This research is qualitative in nature, employing a library research method and using literary texts as the object of analysis. The data source used in this study is the Arabic novel Himār Al-Hakīm by Taufiq Al-Hakim, published by Maktabah Misr in 1990 (147 pages). The data collection technique used is reading and note-taking. The researcher applies the data analysis model from Miles and Huberman, which includes three stages: data reduction, data presentation, and conclusion drawing, using Carl Thompson’s travel literature theory as an analytical tool. This research reveals three main narrative forms in the novel Himār Al-Hakīm by Taufiq Al-Hakim:(1) Forms of reporting the world (4 data),(2) Forms of revealing the self (4 data), and (3) Forms of representing the others (5 data). The novel reflects characteristics of postcolonial travel writing through subjectivity, self-reflection, and a quest for identity. Al-Hakim blends autobiographical elements with an entertaining and reflective style, while also engaging in othering by portraying Eastern culture as inferior and Western culture as superior. تتكون صورة الذات في الحياة الواقعية غالبًا من خلال نتائج التفاعل بين الهوية الشخصية والضغوط الاجتماعية التي تؤثر على كيفية تصرف الفرد. إن صورة الذات في السياق الاجتماعي ليست شيئًا ثابتًا، بل هي نتيجة لبناء ديناميكي. تهدف هذه الدراسة إلى تحليل صورة الذات لطه حسين ككاتب وشخصية في رواية